Modulation of Immune Response by Gold Nanoparticles Oral Administration to Rats - Farman, Mohammed Abbas; Abood, Walaa Najm (South Eastern European Journal of Public Health, 2024)
Gold nanoparticles (GNPs) are a new chemical compound and have recently been used in many pharmacological applications. This study aims to understand enhanced immune response by the oral administration of gold nanoparticles to rats. Gold nanoparticles are administration once oral at different doses to rats, at 14th day collected sample from all administrated rats. The results were shown no effect on the rats’ weight. Gold nanoparticles were caused elevated significant in the antioxidant enzyme CAT and SOD, while decreased in MAD in the administrated groups at dose dependent manner compared with non-administrated control group. Also, GNPs have immune response through modulation in the enhanced immune cell activation by elevated the level of CD8 and CD4 in the administrated groups at dose dependent manner compared with non-administrated control group with the keep the level of TNF-α no differ within all study groups.